A minireview of effects of maternal diet during pregnancy on postnatal vegetable consumption: Implications for future research (a new hypothesis) and recommendations. Issue 13 (2nd September 2018) - Rohlfs Domínguez, Paloma
ABSTRACT: The flavor of the maternal diet is transferred to the amniotic fluid and in this way the amniotic fluid becomes a transmitter of flavor-related information, developing babies can perceive in uterus. We aimed to review the available evidence regarding the impact of prenatal exposure to flavor on postnatal vegetable-related eating behavior. Studies of our focus have been the ones that have ad hoc examined the association of prenatal experience with vegetable-related flavors with vegetable consumption in children. We have identified that some studies have found this association, against others. Particularly, the first group of studies found an increased vegetable intake at weaning and late childhood associated with prenatal flavor exposure. The second set, instead, did not find this association of variables at early childhood. We propose here that the vegetable type used in these last studies might explain this disparity of results, and suggest the following hypothesis to be tested in the future: prenatal exposure to nonbitter vegetables leads to an increased vegetable consumption at early childhood in comparison to prenatal exposure to bitter vegetables, postnatal exposure to vegetables and no exposure. The experimental design of this hypothesis as well as subsequent recommendations for future research and maternal diet are also here suggested.